Patterns of Macular Edema in Uveitis as Diagnosed by Optical Coherence Tomography in Tertiary Eye Center - Gupta, Sharad; Shah, Dev Narayan; Joshi, Sagun Narayan; Aryal, Manoj; Puri, Lila Raj (Nepalese Journal of Ophthalmology, 2018)
Aim: The aim of the study is to classify the patterns of uveitic macular edema using Optical Coherence Tomography as a diagnostic tool. Methodology: It is the Descriptive, cross-sectional study. All patients fulfilling the diagnostic criteria with Optical coherence tomography diagnosed macular edema were enrolled from 1 January 2012 to 30 June 2013. Patterns of uveitic macular edema were classified. Results: A total of 65 eyes of 47 patients were included. Twenty eight (59.57%) were male. The male to female ratio was 1.5:1. The mean age was 38 years (SD 14.68). Twenty nine patients (61.71%) had unilateral involvement and 18 (38.29%) had bilateral involvement. Forty five eyes of 33 cases (69.23%, 70.21%) had intermediate uveitis, followed by 10 eyes of 7 cases (15.38, 14.9%) of posterior uveitis, 6 eyes of 5 cases (9.23%, 10.63 %) of anterior uveitis and 4 eyes of 2 cases (6.16%,4.2%) of pan-uveitis. Patterns of macular edema were classified: diff use macular edema (DME), cystoid macular edema (CME) and serous retinal detachment (SRD) of which 35 (53.84%) eyes had CME. The etiological diagnosis was found in 7(14.90 %) out of 47 patients. Conclusion: A significant percentage of cases were idiopathic. Macular edema may go unnoticed unless OCT is performed. Macular detachment is an important feature of macular edema that affects visual acuity and is not readily detected by Fundus Fluorescein Angiography (FFA). Optical coherence tomography (OCT) is safe and non-invasive technique and has the potential for measuring changes in retinal thickness and axial extent of edema.